Gestão e trabalho na universidade: as recentes reformas do estado e da educação superior e seus efeitos no trabalho docente na UEMG - Neide Elisa Portes dos Santos (2014)
This thesis sought to identify the effects of the recent reforms of state and higher education in teaching at the University of Minas Gerais. Approaches to research were qualitative and quantitative. The empirical research was conducted at the University of Minas Gerais, Belo Horizonte campus and included analysis of institutional and official documents, the application of questionnaires to the teachers of the institution and conducting semi-structured interviews with management of the institution and with two representatives of the teacher movement of the institution. The questionnaires were administered in two units - the School of Design and the School of Education. We opted for both these units count with the highest number of teachers and courses possess Post-graduate studies - subject to profound changes in teaching. The survey found that the reforms for higher education are not compiled into a single document. Are therefore diluted the legal framework that regulates this level of education as well as in public administration concerning the measures in Minas Gerais. Reforms of State imposed from 2003 comprising the last three governments of Minas Gerais had scoped the modernization of the state and were realized through the implementation of the policy called "management shock" that begins in 2003. In the analyzed period, although it was identified as a structural element of the reform of State, the enactment of Law No. 100 of 2007, to establish the system welfare of civil servants in Minas Gerais, promoted a change in the form of hiring these subjects , moved from "temporary workers" (employees hired for a specified period) to workers with permanent contracts predetermined duration - a hybrid category that moves between the public official and employee with permanent contract with a temporary contract. From the definitions of regulation presented by Barroso (2006) and Maroy (2011), we sought to further identify the mechanisms of regulation of labor relations in the analyzed context and vision of subjects concerning the state reforms and higher education, as well as their working conditions. Among these regulatory mechanisms, we highlight the individual performance evaluation whose results serve as reference for the calculation of performance bonuses. The analytical categories used were: teaching career, working conditions, insecurity and work intensification. This study it can be inferred that the university career lies in the institutionalization process, and that even with the changes in the condition of the employee - for temporary contract for an indefinite period, labor relations at the institution remain precarious . Moreover, it is observed that teachers although they claim not to notice changes in your workflow resulting from the modernization of the State, these have been subjected to more subtle forms of work intensification as filling out forms of performance evaluation and the increased demand for participation and engagement in collegiate institutions and the process of assessing individual performance tasks requiring self as: participation in committees for monitoring and evaluation and monitoring of results by the teacher himself.